2020
DOI: 10.12998/wjcc.v8.i14.2977
|View full text |Cite
|
Sign up to set email alerts
|

Role of shear wave elastography in the evaluation of the treatment and prognosis of supraspinatus tendinitis

Abstract: BACKGROUND Supraspinatus tendinitis recurs easily after treatment. One of the main reasons is the lack of objective tools for the efficacy evaluation. Shear wave elastography (SWE) can quantitatively analyze the tissue elasticity of region of interest by measuring the Young’s modulus (YM) value. AIM To explore the role of SWE in the efficacy and prognostic evaluation of supraspinatus tendinitis. METHODS Eighty-seven patients with supraspinatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Zhou et al explored the value of SWE in the treatment efficacy and prognostic evaluation of supraspinatus tendinopathy ( 3 ). Supraspinatus treatment ranged from non-pharmacological management to local injection based on the reported pain visual analog scale (VAS) of the subject.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhou et al explored the value of SWE in the treatment efficacy and prognostic evaluation of supraspinatus tendinopathy ( 3 ). Supraspinatus treatment ranged from non-pharmacological management to local injection based on the reported pain visual analog scale (VAS) of the subject.…”
Section: Resultsmentioning
confidence: 99%
“…Dynamic SE (SWE) uses an acoustic radiation force to create and propagate shear waves. This method measures the shear wave speed to evaluate mechanical properties of tissues to visualize tissue displacements to allow the examiner to infer information regarding the tissular biomechanics (1)(2)(3). Both methods are operator-dependent and have yielded favorable inter-rater reliability (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, covalent cross‐linking between fibrin proteins causes ECM hardening. Previous studies have suggested that transforming growth factor‐β is closely related to cancer cells, and can stimulate fibroblasts to secrete excessive collagen fibers, leading to an increase in ECM stiffness 39 . Provenzano et al 40 reported that tissue stiffening was related to the linearization of collagen fibers.…”
Section: Discussionmentioning
confidence: 99%